Scrub Typhus in Intensive Care Unit in Kathmandu – A case series from a tertiary center - Rajkarnikar, Ruja; Paudyal, Bidhan Raj; Awale, Ayushi; Shrestha, Sanjeev; Sharma, Lucky; Pant, Subash; Shrestha, Sanjeet K (Nepalese Respiratory Journal, 2022)
Scrub typhus is a rickettsial zoonosis caused by Orientia tsutsugamushi which can cause focal or disseminated vasculitis & perivasculitis in various body systems. It is endemic in many parts of Nepal & has been neglected & under-detected. We clinically assessed six patients from a intensive care unit in a tertiary hospital in Nepal that tested positive for scrub typhus using IgM ELISA & analyzed their profiles. Out of six patients, three were male & three were female with a mean age of 44.6 years. All six patients had chief complaints of fever & myalgia. Four patients presented with eschar. Three patients presented with septic shock while one presented with septicemia and meningoencephalitis. Only one patient had elevated white cell counts. Four out of six patients had transaminitis. Thrombocytopenia was present in two patients. Hypoalbuminemia was present in three patients. All cases tested negative for dengue, malaria, brucella, Leptospira, leishmania, salmonella & tuberculosis. This study points out the need for raising the index of suspicion & early screening of scrub typhus in patients with fever & laboratory findings of liver dysfunction or thrombocytopenia even with normal white cell counts.